2017
DOI: 10.3390/molecules22101645
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Biomedical Applications of Zerumbone and the Techniques for Its Extraction from Ginger Rhizomes

Abstract: Zerumbone (ZER) is a phytochemical isolated from the subtropical Zingiberaceae family and as a natural compound it has different biomedical properties such as antioxidant, anti-inflammatory anti-proliferative activity. ZER also has effects on angiogenesis and acts as an antitumor drug in the treatment of cancer, showing selective toxicity toward various cancer cell lines. Several techniques also have been established for extraction of ZER from the rhizomes of ginger. This review paper is an overview of recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 116 publications
(117 reference statements)
0
36
0
2
Order By: Relevance
“…Although pharmaceutical drugs are one of the widely used options for treating several diseases including cancer, these drugs have critical side effects as well as high cost of treatment. For this reason, traditional and herbal medicine has attracted increasing attention due to its cost‐effectiveness and relative safety compared with pharmaceutical drugs (Kalantari et al, ). In line with this notion, several studies showed that such traditional medications exert protective role on ALI progression by regulating JNK signaling and oxidative stress‐mediated cell death (Chen et al, ; Lu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmaceutical drugs are one of the widely used options for treating several diseases including cancer, these drugs have critical side effects as well as high cost of treatment. For this reason, traditional and herbal medicine has attracted increasing attention due to its cost‐effectiveness and relative safety compared with pharmaceutical drugs (Kalantari et al, ). In line with this notion, several studies showed that such traditional medications exert protective role on ALI progression by regulating JNK signaling and oxidative stress‐mediated cell death (Chen et al, ; Lu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the following discussion, the plant source names that authors mentioned in their articles are used irrespective of their current taxonomic classification. There have been extensive studies on zerumbone regarding various biological activities [32], including anti-inflammatory activity in acute lung injury after lipopolysaccharide (LPS) administration in mice [33], antiparasitic activity in protozoa [34], antioxidant, gastroprotective, antisecretory and anti-Helicobacter pylori activities [35], and protection of pancreatic β cell in high glucose induced apoptosis [36]. Similarly, it is reported to be effective in anticancer activity in human breast cancer [37], mouse skin cancer [38] and human cervical cancer cell lines [39].…”
Section: Resultsmentioning
confidence: 99%
“…The study showed phlain I, phlain III, (E)-1-(3,4-dimethoxyphenyl) buta-1,3-diene, (E)-1-(2,4,5-trimethoxyphenyl) buta-1,3-diene, and (−)-β-sesquiphellandrene as the antiinvasive chemical constituents from Z. cassumunar rhizomes [16]. Moreover, zerumbone, furanodienone, germacrone, and terpinen-4-ol were isolated from this plant and showed potent antiproliferative activities against various cancer cell lines [17][18][19][20].…”
Section: Inhibitory Activity Of Extract Fractions and Compounds Fromentioning
confidence: 95%